2011
DOI: 10.1177/1471301211422761
|View full text |Cite
|
Sign up to set email alerts
|

Does a ‘Singing Together Group’ improve the quality of life of people with a dementia and their carers? A pilot evaluation study

Abstract: Ten people with dementia (PWD) and their family carers participated in a Singing Together Group for 10 weeks and measures of mood, quality of life, PWD's behavioural and psychological problems, activities of daily living and cognitive status were measured at pre, post and 10-week follow-up. Engagement levels were monitored during the sessions and care partners asked to rate each session. Additional qualitative information was obtained through interview pre-post and at follow-up and subjected to thematic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
243
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(271 citation statements)
references
References 42 publications
12
243
0
3
Order By: Relevance
“…They were no longer strangers as one stated, they 'recognized each other'. Given the fact that the older people often experience loss and grief of loved ones such as family members or friends (Flood 2005), the social aspect of singing group attendance seemed to provide them with the much-needed psychosocial support, which is also congruent with previous findings about social benefits of choir participation (Bailey and Davidson 2005;Camic et al 2011;Creech et al 2013;Hillman 2002;Joseph 2009;Lally 2009;Lehmberg and Fung 2010;Livesey et al 2012;Gembris 2012). It was clear that they were motivated by this experience of fellowship, such that they kept investing their time and efforts to attend the singing group.…”
Section: • Everybody Wants To Talk To Each Other; We've Got a New Netsupporting
confidence: 80%
See 1 more Smart Citation
“…They were no longer strangers as one stated, they 'recognized each other'. Given the fact that the older people often experience loss and grief of loved ones such as family members or friends (Flood 2005), the social aspect of singing group attendance seemed to provide them with the much-needed psychosocial support, which is also congruent with previous findings about social benefits of choir participation (Bailey and Davidson 2005;Camic et al 2011;Creech et al 2013;Hillman 2002;Joseph 2009;Lally 2009;Lehmberg and Fung 2010;Livesey et al 2012;Gembris 2012). It was clear that they were motivated by this experience of fellowship, such that they kept investing their time and efforts to attend the singing group.…”
Section: • Everybody Wants To Talk To Each Other; We've Got a New Netsupporting
confidence: 80%
“…Previous research has highlighted positive social consequences associated with participating in music for older people, such as socializing with others, feeling supported and experiencing belonging and group membership (Livesey et al 2012;Lally 2009;Creech et al 2013;Joseph 2009;Hillman 2002;Lehmberg and Fung 2010;Camic et al 2011;Bailey and Davidson 2005). Musical activities provide a structure and offer a way to sustain social interaction with others (Gembris 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent research involving PWD and carers in singing groups suggested that learning new lyrics, melodies and movement was possible for people in the early and mid-stages of dementia (Camic, Williams, & Meeten, 2013). Likewise, in the present study, we were able to substantiate that the PWD were able to demonstrate new learning within a gallery setting.…”
Section: Cognitive Capacitiessupporting
confidence: 76%
“…In a study in the United Kingdom, 10 dyads of people with dementia and their family caregivers participated in a singing group that met for 10 weekly 90 minute sessions. While the quantitative measures failed to reveal significant improvements, qualitative data suggested both caregivers and people with dementia had positive experiences, which included a sense of social connectedness, focusing on the strengths of the person with dementia rather than the weaknesses and supporting their relationship (Camic et al, 2013).…”
Section: Choral Singing For People With Dementia With Their Caregiversmentioning
confidence: 99%